Decoding paraneoplastic neuromyelitis optica: a multi-omics investigation of tumor-driven T and B cell dynamics - Huang, Wenjing; Lin, Ruyu; Zeng, Xianyi; Wang, Hai; Yan, Jichun (Frontiers in Immunology, 2025)
A significant subset of Neuromyelitis Optica Spectrum Disorder (NMOSD) cases occurs as a paraneoplastic syndrome, where an underlying tumor triggers a devastating autoimmune attack against the central nervous system. This autoimmune response is driven by pathogenic aquaporin-4 autoantibodies (AQP4-IgG), likely initiated by the tumor’s expression of AQP4 in a phenomenon of molecular mimicry. Understanding the precise immune mechanisms that link a patient’s cancer to their neurological disease is critical for early diagnosis of the occult malignancy and for improved patient outcomes. This review explores how multi-omics technologies are revolutionizing the investigation of T and B cell functional dynamics in this specific context, offering unprecedented resolution into the pathogenesis of paraneoplastic NMOSD. The application of integrated multi-omics—including genomics, epigenomics, transcriptomics (particularly single-cell RNA-seq), proteomics, and metabolomics—provides a holistic framework to dissect the specific immune response directed against both the tumor and the CNS. Transcriptomics, notably scRNA-seq, can deconstruct the heterogeneity of tumor-infiltrating and circulating T and B cells to identify the pathogenic subsets responsible for the autoimmune pathology. Proteomics can aid in identifying tumor-specific biomarkers, while metabolomics offers insights into the metabolic vulnerabilities of the autoreactive immune cells. Multi-omics analyses reveal the cellular and molecular cascade of the paraneoplastic response. High-throughput T-cell receptor (TCR) and B-cell receptor (BCR) sequencing provides direct evidence of oligoclonal expansions, identifying the specific T and B cell clones that likely recognize shared AQP4 epitopes on both the cancer cells and CNS astrocytes. These expanded B cells show hallmarks of a mature, antigen-driven response, including class-switching and affinity maturation of the pathogenic AQP4-IgG. Furthermore, analyses of T cell dynamics reveal a pro-inflammatory environment, with functional impairment of regulatory T cells (Tregs) and a skewed balance towards Th17 and Th1 cells, which is likely initiated by the tumor and perpetuated in the CNS via critical T-B cell interactions, such as the IFN-I → B-cell → IL-6 → pathogenic Th17 axis. Despite these insights, substantial challenges remain in translating these findings into clinical practice. A key hurdle is using multi-omics to develop a reliable molecular signature that can distinguish paraneoplastic from idiopathic NMOSD at diagnosis, thereby streamlining cancer screening for high-risk patients. Advanced computational tools, including AI and machine learning, are needed to integrate the immense volume of data and identify the subtle differences. Future research must prioritize the analysis of longitudinal samples (before and after tumor treatment) and the functional validation of the identified pathogenic pathways. In conclusion, multi-omics is profoundly enhancing our understanding of how tumors can initiate and sustain a specific, targeted autoimmune response in paraneoplastic NMOSD. This deep mechanistic investigation not only promises to improve diagnostics and personalized therapies for these complex patients but also serves as a powerful model for understanding other paraneoplastic syndromes, ultimately bridging the fields of oncology and neuroimmunology.